EFFECTIVENESS OF POPULATION REGISTRATION, MANAGEMENT AND DOCUMENT SERVICES (POEDAK) DISPENDUKCAPIL IN IMPROVING THE QUALITY OF POPULATION ADMINISTRATION SERVICES IN SEKAPUK VILLAGE, UJUNG PANGKAH GRESIK - Nadiah, Amelia Ruli; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of implementing e-government through the Population Registration, Management, and Document Service (POEDAK) application developed by the Dispendukcapil in Sekapuk Ujung Pangkah Gresik Village. Method: A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model. Results: The findings reveal that POEDAK has improved the efficiency of population administration services by reducing queues, accelerating the issuance of documents, and enhancing transparency and accountability in public services. Nevertheless, challenges remain, including low levels of digital literacy among residents, limited internet access, and technical difficulties in application usage. Efforts by the village government in conducting outreach and training have contributed to better community understanding and gradual adoption of digital services. Novelty: This research highlights how a village-level digital application can serve as a practical model for inclusive e-government implementation in rural contexts, emphasizing the interplay between technological infrastructure, community digital education, and responsive system management as critical factors for sustainable success.